Identifying skill gaps and tailoring employee training and development programs to meet organizational needs at MASTER WiZR. - Tanima, Maria Latif (Brac University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2023.